DEVELOPMENT OF SENSORS FOR MONITORING THE AVIAN ENVIRONMENT WITH EMPHASIS IN THERMAL CONTROL - de Oliveira, M. E.; de Oliveira, R. L. Z.; de Souza, M. F. L. Z.; Harada, E. S.; Tech, A. R. B. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Among the productive sectors of meat, the poultry sector has been gaining space and growing. The last decade, a problem with the pet began to gain weight and to grow growing notably, mainly in physiological animals as indicators of the animal comfort condition. In 2016, Brazil was the world's second largest producer of chicken protein, with 12.9 billion tons, and also the largest exporter with 4.304 million tons of chicken meat. Thus, the work was done to evaluate a wireless communication system with temperature sensors and risks boarded in an experimental aviary located at the Fernando Costa campus in Pirassununga / SP, while the data was filtered by the database MySql. Aimed at the thermal control of the aviary environment, considering the importance of the environmental impact on the productivity and welfare of the broiler chicken. The results were as follows: the developed sensor system was able to measure the internal temperature, the average processing time of data collected in the cloud.